Recent Development in N-Auxilixary-Assisted Intramolecular Amination for Amine Substrates - Wang, Chao; Han, Jian; Zhao, Yingsheng (Synlett, 2015)
Direct coupling of N–H with C–H has aroused great attention in the last decades; during which the directing-group-assisted intramolecular C–N bond formation via transition metal has been achieved significant progress. Herein, we highlight the recent development in the directing-group-assisted intramolecular amination for amine substrates to build the important N-containing heterocyclic compounds.1 Introduction2 Triflamide-Promoted Intramolecular Amination3 Picolinamide-Assisted Intramolecular Amination4 Palladium-Catalyzed Intramolecular Amination under Assistance of Oxalyl Amide5 Conclusion
Keywords: amination; cyclization; transition metals; C–H activation; directing groups